2021
DOI: 10.3389/fgene.2021.723001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Novel Prognosis-Related Genes Through Transcriptome Sequencing, Bioinformatics Analysis, and Clinical Validation in Acute Myeloid Leukemia

Abstract: Background: Acute Myeloid Leukemia (AML) is a complex and heterogeneous hematologic malignancy. However, the function of prognosis-related signature genes in AML remains unclear.Methods: In the current study, transcriptome sequencing was performed on 15 clinical samples, differentially expressed RNAs were identified using R software. The potential interactions network was constructed by using the common genes between target genes of differentially expressed miRNAs with transcriptome sequencing results. Functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Due to the lack of corresponding miRNA expression data in the TCGA-LAML and GTEx datasets, we searched PubMed for studies on these miRNAs in AML. From previous literature, the expression of miR-93-5p [ 26 , 27 ], miR-124-3p [ 28 , 29 ], miR-185-5p [ 30 , 31 ], miR-20a-5p [ 32 , 33 ], and miR-17-5p [ 34 , 35 ] differs in AML patients compared to healthy controls. Meanwhile, miR-106a-5p was consistently overexpressed in settings where AML was resistant to therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the lack of corresponding miRNA expression data in the TCGA-LAML and GTEx datasets, we searched PubMed for studies on these miRNAs in AML. From previous literature, the expression of miR-93-5p [ 26 , 27 ], miR-124-3p [ 28 , 29 ], miR-185-5p [ 30 , 31 ], miR-20a-5p [ 32 , 33 ], and miR-17-5p [ 34 , 35 ] differs in AML patients compared to healthy controls. Meanwhile, miR-106a-5p was consistently overexpressed in settings where AML was resistant to therapy.…”
Section: Resultsmentioning
confidence: 99%
“…According to the GEPIA portal (http://gepia.cancer-pku.cn, accessed on 10 July 2023), higher expression of CXCL3, CXCL5, and PPBP in AML cells is associated with poorer prognoses for patients with the described leukemia [9,52]. Other bioinformatic analyses also confirmed that higher CXCL5 expression in AML cells is related to poorer prognoses [57]. According to the UALCAN portal (https://ualcan.path.uab.edu, accessed on 10 July 2023), there is a tendency (p = 0.093) for poorer prognoses with higher PPBP expression in AML cells [8,10].…”
Section: The Association Of the Expression Levels Of Cxcr1 And Cxcr2 ...mentioning
confidence: 87%
“…The level of CXCR6 expression in the blood of AML patients may be associated with better outcomes [ 57 ], but conflicting results have been reported [ 51 ].…”
Section: Ligand Cxcr6: Cxcl16mentioning
confidence: 99%
“…As a result, they can be used as diagnostic, prognostic, and therapeutic biomarkers at various stages of leukemia. Furthermore, growing evidence suggests that miRNAs could be used as markers in diagnosis and treatment in the early stages of the disease or following chemotherapy (21,22).…”
Section: Discussionmentioning
confidence: 99%